Functional Balancing of the Hypoxia Regulators RAP2.12 and HRA1 Takes Place in vivo in Arabidopsis thaliana Plants - Giuntoli, Beatrice; Licausi, Francesco; van Veen, Hans; Perata, Pierdomenico (Frontiers in Plant Science, 2017)
Plants are known to respond to variations in cellular oxygen availability and distribution by quickly adapting the transcription rate of a number of genes, generally associated to improved energy usage pathways, oxygen homeostasis and protection from harmful products of anaerobic metabolism. In terrestrial plants, such coordinated gene expression program is promoted by a conserved subfamily of ethylene responsive transcription factors called ERF-VII, which act as master activators of hypoxic gene transcription. Their abundance is directly regulated by oxygen through a mechanism of targeted proteolysis present under aerobic conditions, which is triggered by ERF-VII protein oxidation. Beside this, in Arabidopsis thaliana, the activity of the ERF-VII factor RAP2.12 has been shown to be restrained and made transient by the hypoxia-inducible transcription factor HRA1. This feedback mechanism has been proposed to modulate ERF-VII activity in the plant under fluctuating hypoxia, thereby enhancing the flexibility of the response. So far, functional balancing between RAP2.12 and HRA1 has been assessed in isolated leaf protoplasts, resulting in an inverse relationship between HRA1 amount and activation of RAP2.12 target promoters. In the present work, we showed that HRA1 is effective in balancing RAP2.12 activity in whole arabidopsis plants. Examination of a segregating population, generated from RAP2.12 and HRA1 over-expressing plants, led to the first quantitative proof that, over a range of either transgene expression levels, HRA1 counteracts the phenotypic and transcriptional effects of RAP2.12. This report supports the occurrence of fine-tuned regulation of the hypoxic response under physiological growth conditions.